“Label” Competition: Field Theory Insights into Inter-Governmental Competition and Transformation Path Among Chinese Cities - Litu Ji (Studies in Social Science & Humanities, 2024)
Inter-governmental competition has always been a crucial area of exploration in understanding the behavior of governments. Against the backdrop of contemporary China, the development of the Internet and the increasing influence of communication media have brought to light the growing significance of “Labels” that encapsulate the internal functions, characteristics, or relative advantages of regions in assessing the capabilities of local governments. In this process, the creation and dissemination of urban “Labels” not only drive the new transformation path of inter-governmental competition but also contribute to the reform of the official construction of the capital structure and internal Habitus of urban government field. Based on Field theory, a systematic investigation is conducted on the urban “Labels” generated with the development and influence of the Internet and communication media. In-depth analysis of the logic of urban “Labels” generation reveals that the competitive strategy of urban governments is gradually shifting from the previous “clear distinction between Top-Down” mode to a comprehensive path of “integration of Top-Down and Bottom-Up.” At the same time, the evaluation mechanism has shifted from a single “indicator” evaluation to a more comprehensive judgment focusing on “events,” and the path has shifted from simple “competition” to “competitive cooperation” mode.